Nurse and midwife researcher collaboration in eastern sub‐Saharan Africa: a social network analysis. (13th September 2019) - Cato, K.D.; Sun, C.; Dohrn, J.; Ferng, Y.‐h.; Klopper, H.C.; Larson, E.
Abstract : Aim: To investigate the collaborative networks among expert clinical nurse and midwifery researchers in eastern and southern Africa. Methods: Thirty‐eight clinical nurse and midwifery researchers completed an online survey to analyse collaboration between respondents. Data were analysed using social network analysis, generating a network map and associated measurements. Results: Regional collaboration was poor. Those links that did exist centred on geographic proximity and participation in regional and international organizations. Conclusion: These results help us to understand better ways to strengthen and support nursing and midwifery clinical research in eastern and southern Africa. Implications for nursing policy: Clinical nursing and midwifery research capacity building efforts should focus on supporting collaboration networks among individuals and institutions in the region.